Penggunaan Karya Seni Tanpa Izin pada Sistem Pembelajaran AI dalam Prespektif Hak Cipta di Indonesia - Vedanti, Kausalya Ayu (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
The significant development of technology has given rise to many new technologies that provide convenience in various fields of human work, one of which is the emergence of Artificial Intelligence Art Generator technology as an innovation in the world of art. AI Art will create images according to user requests entered in the description column, without the need to have a talent for drawing, someone can produce works of art. Behind this convenience, there are violations of the copyright of works of art due to the use of works as input data without permission for commercial purposes carried out by the AI ​​Art company.